Предмет: Алгебра, автор: FlyFo

(2х+1) (2х-1)>2(х+0,5)^2 решить уравнение

Ответы

Автор ответа: julyap
0
(2x+1)(2x-1)>2*(x+0.5)^{2} \4 x^{2} -1>2( x^{2} +0.25+x)\4 x^{2} -1>2 x^{2} +0.5+2x\4 x^{2} -1-2 x^{2} -0.5-2x>0\2 x^{2} -2x-1.5>0\2 x^{2} -2x-1.5=0 \ D=4+12=16\ sqrt{D} =4\  x_{1} = frac{2+4}{4} = frac{6}{4} =1.5\ x_{2} = frac{2-4}{4} = frac{-2}{4} =-0.5\2 x^{2} -2x-1.5=2(x+0.5)(x-1.5)
 
       +                      -                               +
-------------|---------------------------|------------------------->
             -0.5                              1.5                            x

x∈ (- infty;-0.5)U(1.5;+  infty)


Ответ: x∈ (- infty;-0.5)U(1.5;+ infty)  
Похожие вопросы
Предмет: Математика, автор: про100Slap